Avaliação dos efeitos da administração oral do firocoxib sobre a quebra da barreira hematoaquosa induzida por paracentese em gatos saudáveis e com sorologia positiva para toxoplasmose - Schroder, Deise Cristine (2015)
The objective was to evaluate the efficacy of firocoxib in preventing the blood-aqueous barrier breakdown in healthy cats and those with positive serology for toxoplasmosis. Thirty-two cats divided into four groups (n=8/each). The healthy control (HC) and toxoplasmosis control (TC) groups, were composed respectively of healthy cats and cats with positive serology for toxoplasmosis, while healthy firocoxib (HF) and toxoplasmosis firocoxib (TF) groups, were composed respectively of healthy cats and cats with positive serology for toxoplasmosis who had received previous treatment with orally firocoxib (5 mg/kg), twenty-four and one hour before the experimental induction of uveitis. Under anesthesia 0.2 mL of baseline aqueous humor was collected via aqueocentesis. One hour later, the same procedure was repeated and inflamed aqueous samples were collected. Aqueous samples were conditioned at -80°C for subsequent measurement of the levels of prostaglandin E2 (PGE2) and total proteins. In the aqueous samples of TC and TF groups, anti-Toxoplasma gondii IgG specific antibodies were titrated. PGE2 and total protein levels increased significantly in inflamed aqueous humor in comparison to baseline aqueous samples (p<0.05). At baseline aqueous humor, levels of PGE2 in TC group and total protein in HF and TF groups were increased significantly, in comparison with the other groups (p<0.05). Anti-Toxoplasma gondii IgG specific antibodies were found only in inflamed aqueous humor, and aqueous titers did not change significantly between TC and TF (p=0.1051). Although we have observed that aqueous humor PGE2 levels were significantly higher in seropositive cats in baseline aqueous humor, such increase was not able to break the blood-aqueous barrier and cause anterior uveitis. Firocoxib did not prevent intraocular inflammation after aqueocentesis, in healthy and toxoplasmosis-seropositive cats.